1994
DOI: 10.1007/bf00019047
|View full text |Cite
|
Sign up to set email alerts
|

Photoinhibition of photosynthesis in chilled potato leaves is not correlated with a loss of Photosystem-II activity

Abstract: When 23 °C-grown potato leaves (Solanum tuberosum L.) were irradiated at 23 °C with a strong white light, photosynthetic electron transport and Photosystem-II (PS II) activity were inhibited in parallel. When the light treatment was given at a low temperature of 3 °C, the photoinhibition of photosynthesis was considerably enhanced, as expected. Surprisingly, no such stimulation of photoinhibition was observed with respect to the PS II function. A detailed functional analysis of the photosynthetic apparatus, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 54 publications
(56 reference statements)
6
99
1
1
Order By: Relevance
“…1: light-induced loss of electron transport at 23°C proceeded independently of lipid peroxidation whereas chilling stress in the light simultaneously caused photosynthesis inhibition and lipid photooxidation. Moreover, strong light stress at 3°C was previously observed to cause an O2-dependent selective loss of PSI function which was mimicked at 230C by illuminating leaves infiltrated with a SOD inhibitor [8], suggesting that 02-is involved in the lipid peroxidation phenomena reported here. The present study (Table 1, Fig.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…1: light-induced loss of electron transport at 23°C proceeded independently of lipid peroxidation whereas chilling stress in the light simultaneously caused photosynthesis inhibition and lipid photooxidation. Moreover, strong light stress at 3°C was previously observed to cause an O2-dependent selective loss of PSI function which was mimicked at 230C by illuminating leaves infiltrated with a SOD inhibitor [8], suggesting that 02-is involved in the lipid peroxidation phenomena reported here. The present study (Table 1, Fig.…”
Section: Discussionsupporting
confidence: 61%
“…A previous study of light-treated potato leaves [8] has shown that photoinhibition of photosynthetic electron transport at 23°C (growth temperature) and at 3°C are different phenom- ena. This is confirmed by the data of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tais mudanças podem representar perda de eficiência fotoquí-mica pelas plantas e, como consequência, a diminuição da fotossíntese. Além disso, o maior desempenho das reações de oxi-redução do FSI [R 0 /(1-R 0 )] no Catongo pode ser explicado pelo fato de o FSI ser mais tolerante ao excesso de radiação do que o FSII (Havaux & Davaud, 1994), o que permite a este genótipo utilizar a pequena quantidade de energia absorvida para redução da ferredoxina e do NADP + . Por outro lado, a fotoinibição, nesse genótipo, também pode estar relacionada com a ausência de antocianinas em suas folhas (Figueira & Cascardo, 2001), pigmentos que conferem efeito fotoprotetor ao aparato fotossintético (Close & Beadle, 2003).…”
Section: Trocas Gasosas Foliaresunclassified